Multifunctional EuYVO4 nanoparticles coated with mesoporous silica - Justino, Larissa G.; Nigoghossian, Karina [UNESP]; Capote, Ticiana S.O. [UNESP]; Scarel-Caminaga, Raquel M. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Caiut, José Maurício A. (Elsevier, 2016)
Mesoporous structures are interesting materials for the incorporation of dyes, drugs, and luminescent systems, leading to materials with important multifunctionalities. In a very unique way, these guest/host materials combine the high stability of inorganic systems, new guest-structuring features, and adsorption mechanisms in their well-defined pores. This work evaluates the luminescent properties of rare earth-doped YVO4 nanoparticles coated with a mesoporous silica shell. The use of two different synthesis methodologies allowed for particle size control. The crystalline phase emerged without further heat treatment. The mesoporous shell decreased undesirable quenching effects on YVO4:Eu3+ nanoparticles and rendered them biocompatible. The materials prepared herein could have interesting applications as luminescent markers or drug release systems.
Keywords: Luminescence; Rare earth; Surface modification